Demographic profile and risk factors associatedwith depression among elderly in rural area of Dhule district in Maharashtra - Sarika P. Patil; Mukesh S. Bawa; Sushant S. Chavan; Vikrant S. Pagar (International Journal of Health and Clinical Research, 2021)
Background: Approximately 11-18% of adults aged 60 and over suffers from a mental disorder. According to the World Health Organization (WHO) report, patients over 55 years with depression have a four times higher death rate than those without depression. Early recognition, diagnosis, and initiation of treatment for depression in older people present opportunities for improving their quality of life, preventing suffering or premature death and maintaining optimal levels of function and independence.This study aims to find out association of various risk factors with depression among elderly people.Methods: Across-sectional study was done in rural households in the field practice area of a tertiary health care hospital. A total of 240 elderly persons were interviewed using pretested and predesigned questionnaire from GDS-30. Data was analysed using percentages and χ2-test. Results: The prevalence of depression in elderly persons was 26.6%; among these, 18% were mildly depressed and 8.3% severely depressed. Depression was more prevalent in those who were physically inactive (48.27%) than those who were active (14.37%) ( p = 0.000). About 26.41% of illiterates were found to be depressed than literate ones (24.7%). significant association was found between illiteracy and depression (χ2 = p = 0.004). Significant association was found betweenage related morbidities such as neurological disorders, locomotor disorder and depression.Conclusion:Prevalence of depression among elderly was found to be 26.6%. Significant association was found betweenphysical inactivity,locomotor disorder, neurological disorder and depression.